Digital leaders: political leadership in the digital age - Villaplana, F. Ramón; Fitzpatrick, Jasmin (Frontiers in Political Science, 2024)
This paper delves into the concept of digital leadership in contemporary democracies, considering the impact of the digital age on politics and, consequently, on political leadership. In our view, with the spread of radio stations first, then televisions, and finally the web, leadership has evolved through three great stages: broadcast, telegenic and digital. The web, and social media in special, have reshaped democracies and political interactions both at macro, meso, and micro levels. With Obama as forefather and across different political ideologies, a new generation of politicians as Beppe Grillo, Justin Trudeau, Giorgia Meloni or Sanna Marin, among others, shows how leaders are adapting to a highly digitalized political environment. As we understand it, leaders with good digital media abilities need to excel in three skills –presence, interaction and engagement– and would have two main attributes: reliability and relatability. We also consider that the digitalization of leadership deepens the personalization and presidentialization phenomena in politics and under certain circumstances may provide cases of so-called hyper-leadership more frequently.